2019
DOI: 10.1371/journal.pone.0214805
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive technique to evaluate the muscle fiber characteristics using q-space imaging

Abstract: Background Skeletal muscles include fast and slow muscle fibers. The tibialis anterior muscle (TA) is mainly composed of fast muscle fibers, whereas the soleus muscle (SOL) is mainly composed of slow muscle fibers. However, a noninvasive approach for appropriately investigating the characteristics of muscles is not available. Monitoring of skeletal muscle characteristics can help in the evaluation of the effects of strength training and diseases on skeletal muscles. Purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…26,27 For example, muscle cells in tibialis anterior can exhibit a larger diameter than those of soleus muscle. 28 The phantom measurements showed that B 0 correction could partially improve the quantitative accuracy and reproducibility between the two different sites. Thus we performed B 0 correction for the in vivo data.…”
Section: Discussionmentioning
confidence: 94%
“…26,27 For example, muscle cells in tibialis anterior can exhibit a larger diameter than those of soleus muscle. 28 The phantom measurements showed that B 0 correction could partially improve the quantitative accuracy and reproducibility between the two different sites. Thus we performed B 0 correction for the in vivo data.…”
Section: Discussionmentioning
confidence: 94%
“…As body weight loss observed after DEX treatment is primarily attributable to skeletal muscle atrophy [ 30 ], the reduction in body weight and the associated reduction in gastrocnemius and tibialis anterior mass found in our DEX-treated rats were not incomprehensible. Gastrocnemius and tibialis anterior are skeletal muscles with relatively more fast-twitch fibers and fewer slow-twitch fibers, whereas the soleus is the opposite [ 31 , 32 ]. DEX has been shown to act primarily on muscles that contain type IIb fast-twitch fibers [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, muscle atrophy was observed only in gastrocnemius and tibialis anterior, which may be associated with increased expression of atrogin-1/MAFbx and MuRF1, but not in soleus, which is consistent with previous findings [ 33 ]. Although the weight of the extensor digitorum longus tended to decrease in the DEX group compared with the control group, the extensor digitorum longus is a smaller muscle that lies deeper than gastrocnemius and tibialis anterior muscles, and the difference was difficult to identify after DEX-induced muscle atrophy [ 31 , 33 ]. Based on the previous research and our findings, we suggest that DEX-induced fast-twitch muscle atrophy may be associated with increased expression of atrogin-1/MAFbx and MuRF1.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the non-specificity of muscular T1 and T2 times limits the ability to reproducibly determine fiber type composition in clinical routine. More recent investigations have however presented encouraging approaches utilizing quantitative methods of diffusion-weighted MR (q-space imaging) and were able to differentiate different muscles (by their fiber composition) in mice (33).…”
Section: Standard Spin-echo Mr Imagingmentioning
confidence: 99%